Hematological Parameters and Genetic Diversity in Acute Myeloid Leukemia and their Clinical Prognosis - معلّا يحيى; جرجس ميخائيل; يازجي هيثم; خميس عطية (Latakia University Journal -Medical Sciences Series, 2022)
Acute myeloid leukemia (AML) has the highest death rate among all types of hematological neoplasms. Recently, cytogenetic and molecular genetics are crucial in the management, as a consequence of their effect on AML pathogenesis, classification, risk-stratification, prognosis and treatment.100 Syrian adults with Normal Karyotype (NK) newly diagnosed AML patients were included in this study, all cases confirmed histologically and immunohistochemically. Polymerase chain reaction (PCR) was performed on exon 11-12 for FMS-like tyrosine kinase-3 internal tandem duplication (FLT3-ITD) and exon 12 for Nucleophosmin1 (NPM1) using target primers, the electropherograms were analyzed for gene mutations by comparing with the reference DNA sequence. Data were compared and aligned with different sequences using the NCBI BLAST Assembled Genomes tool.FLT3 and NPM1 were detected in 26%, 22 % patients respectively. M2 subtype had the most frequent incidence of diagnosis in AML. FLT3-ITD mutation patients had the highest mean of death cases. Patients with FLT3-ITD and NPM1 mutations have a bad prognosis, where the presence of those mutations was significantly related to high death rates. We can declare according to this study that genetic mutation and variants detection could easily be incorporated into the regimen evaluation of AML patients.